Adhesive composition for foldable display and optical member for foldable display

KR103022717B1Active Publication Date: 2026-09-18NIPPON CARBIDE KOGYO KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020200170106
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-09
Filing Date
2020-12-08
Publication Date
2026-09-18
Estimated Expiration
2040-12-08

Smart Images

  • Figure 112020132704812-PAT00001
    Figure 112020132704812-PAT00001
  • Figure 112020132704812-PAT00002
    Figure 112020132704812-PAT00002
  • Figure 112020132704812-PAT00003
    Figure 112020132704812-PAT00003
Patent Text Reader

Abstract

An adhesive composition for a foldable display and an optical member for a foldable display comprising a (meth)acrylic copolymer comprising a constituent unit derived from a monomer having a hydroxyl group and a constituent unit derived from an alkyl (meth)acrylate monomer, and a crosslinking agent, wherein when an adhesive layer is formed, the storage modulus at -20°C is in the range of 0.05 MPa or more and 0.5 MPa or less, the ratio of the storage modulus at -20°C to the storage modulus at 100°C is 15.0 or less, and the gel fraction is 50 mass% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an adhesive composition for a foldable display and an optical member for a foldable display. Background Technology

[0002] Recently, portable electronic devices known as so-called foldable devices (also called "flexible devices"), such as devices with curved shapes and foldable devices, are becoming widespread. With this proliferation, adhesive compositions equipped with properties suitable for applications in foldable devices are being developed.

[0003] For example, Japanese Patent Publication No. 2017-95653 describes an adhesive for an optical film comprising a (meth)acrylic acid ester copolymer (A), wherein the (meth)acrylic acid ester copolymer (A) comprises: (a1) 9.9 mass% or more and 99.9 mass% or less of a constituent unit derived from an alkyl (meth)acrylic acid ester monomer; (a2) 0.1 mass% or more and 15 mass% of a constituent unit derived from a (meth)acrylic monomer having an amide group; and (a3) ​​0 mass% or more and 19.9 mass% or less of a constituent unit derived from a functional group-containing monomer, which is a (meth)acrylic acid ester monomer not having a plurality of radical polymerizable functional groups; (a4) 0 mass% or more and 90 mass% or less of a constituent unit derived from a (meth)acrylic acid ester monomer other than (a1), (a2) and (a3); wherein the total amount of constituent units derived from (a1), (a2), (a3) ​​and (a4) is 100 mass%, and the glass transition temperature of the (meth)acrylic acid ester copolymer (A) is -70°C or more and -58°C or less, and the weight average molecular weight is greater than 1 million and less than 2.5 million. An adhesive for an optical film is disclosed.

[0004] In addition, for example, Japanese Patent Publication No. 2018-45213 discloses an adhesive for a flexible display for laminating one flexible member and another flexible member constituting a flexible display, wherein the storage modulus (G(-20)) at -20°C is 0.05 MPa or more and less than 1 MPa, and the change rate of elasticity derived by the following equation (1) based on the storage modulus (G(-20)) and the storage modulus (G(40)) at 40°C is 350% or more and 10000% or less. Change rate of elasticity (%) = [G(-20) / G(40)] × 100···(1) The problem to be solved

[0005] Foldable devices are often carried to various locations due to their excellent portability. Consequently, they require durability against rapid changes in ambient temperature. Typically, foldable devices are carried in a folded state. In a folded state, stress caused by the folding becomes concentrated on the adhesive layer at the folded portion. Generally, foldable devices are more prone to defects such as whitening or foaming caused by stress on the adhesive layer at the folded portion when folded compared to when unfolded. Therefore, even if the adhesive layer has excellent durability against rapid temperature changes in the unfolded state, its durability against rapid temperature changes in the folded state tends to be lower.

[0006] For example, an adhesive composition used for bonding a foldable display and an optical member (hereinafter also referred to as "adhesive composition for a foldable display") is required to be able to form an adhesive layer with excellent durability against rapid changes in ambient temperature in a folded state (hereinafter also referred to as "thermal shock resistance").

[0007] Regarding the above-mentioned point, Japanese Patent Publication No. 2017-95653 and Japanese Patent Publication No. 2018-45213 do not mention anything about increasing the durability of the adhesive layer when a folded foldable device is exposed to a rapid change in ambient temperature.

[0008] In addition, since foldable devices repeatedly transition between unfolded and folded states, it is required that the adhesive composition for foldable displays be capable of forming an adhesive layer with excellent bending resistance. Generally, adhesive layers have the characteristic of becoming harder as the temperature decreases. When a bending operation is performed on an adhesive layer in a hard state, whitening or breakage of the adhesive layer may occur. The inventors found that when they increased the stress relaxation of the adhesive layer to improve its bending resistance under low-temperature environments, there was a tendency for the adhesive strength to decrease.

[0009] As described above, it was difficult to improve both bendability and adhesive strength in a low-temperature environment in addition to thermal shock resistance in a folded state in an adhesive composition for foldable displays.

[0010] The problem to be solved by the present invention is to provide an adhesive composition for a foldable display capable of forming an adhesive layer that exhibits excellent thermal shock resistance in a folded state and bendability in a low-temperature environment, and also exhibits good adhesive strength, and an optical member for a foldable display having an adhesive layer formed by said adhesive composition for a foldable display. means of solving the problem

[0011] Specific means for solving the problem include the following forms.

[0012] <1> A (meth)acrylic copolymer comprising a constituent unit derived from a monomer having a hydroxyl group and a constituent unit derived from a (meth)acrylate alkyl ester monomer, and a crosslinking agent,

[0013] An adhesive composition for a foldable display having a storage modulus at -20°C in the range of 0.05 MPa or more and 0.5 MPa or less when an adhesive layer is formed, a ratio of the storage modulus at -20°C to the storage modulus at 100°C (i.e., storage modulus at -20°C / storage modulus at 100°C; hereinafter the same) of 15.0 or less, and a gel fraction of 50 mass% or more.

[0014] <2> When an adhesive layer is formed, the ratio of the storage modulus at -20°C to the storage modulus at 100°C is in the range of 4.5 or more and 15.0 or less, <1> Adhesive composition for foldable displays described in

[0015] <3> The above (meth)acrylic copolymer having a weight average molecular weight of 1 million or more, <1> or <2> Adhesive composition for foldable displays described in

[0016] <4> The glass transition temperature of the above (meth)acrylic copolymer is less than -50℃, <1> ~ <3> An adhesive composition for a foldable display described in any one of the following.

[0017] <5> The above (meth)acrylate alkyl ester monomer comprises at least one monomer selected from the group consisting of 2-ethylhexyl acrylate and i-octyl acrylate, <1> ~ <4> An adhesive composition for a foldable display described in any one of the following.

[0018] <6> The above crosslinking agent is an isocyanate-based crosslinking agent, <1> ~ <5> An adhesive composition for a foldable display described in any one of the following.

[0019] <7> The above isocyanate-based crosslinking agent is hexamethylene diisocyanate, <6> Adhesive composition for foldable displays described in

[0020] <8> further comprising a tackifier, <1> ~ <7> An adhesive composition for a foldable display described in any one of the following.

[0021] <9> The above (meth)acrylic copolymer comprises a constituent unit derived from a monomer having a carboxyl group, <1> ~ <8> An adhesive composition for a foldable display described in any one of the following.

[0022] <10> <1> ~ <9> An optical member for a foldable display having an adhesive layer formed by an adhesive composition for a foldable display described in any one of the following. Effects of the invention

[0023] According to the present invention, an adhesive composition for a foldable display capable of forming an adhesive layer that exhibits excellent thermal shock resistance in a folded state and excellent bendability in a low-temperature environment, and also exhibits good adhesive strength, and an optical member for a foldable display having an adhesive layer formed by said adhesive composition for a foldable display are provided. Specific details for implementing the invention

[0024] Specific embodiments of the present invention will be described in detail below. However, the present invention is not limited in any way to the following embodiments and may be implemented with appropriate modifications within the scope of the purpose of the present invention.

[0025] In this specification, a numerical range indicated by "~" refers to a range that includes the values ​​listed before and after "~" as the minimum and maximum values, respectively.

[0026] In the numerical ranges described stepwise in this specification, an upper or lower limit value described in any numerical range may be substituted with an upper or lower limit value of another numerical range described stepwise. Additionally, in the numerical ranges described in this specification, an upper or lower limit value described in any numerical range may be substituted with a value shown in the examples.

[0027] In this specification, a combination of two or more preferred forms is a more preferred form.

[0028] In this specification, the amount of each component refers to the total amount of the multiple types of substances where there are multiple types of substances corresponding to each component, unless specifically stated otherwise.

[0029] In this specification, "(meth)acrylic copolymer" means a copolymer in which the content of a constituent unit derived from a monomer having a (meth)acryloyl group is 50 mass% or more of the total constituent unit [i.e., the total constituent unit of the (meth)acrylic copolymer].

[0030] In this specification, “(meth)acryl” is a term including both “acryl” and “methacryl,” “(meth)acrylate” is a term including both “acrylate” and “methacrylate,” and “(meth)acryloyl” is a term including both “acryloyl” and “methacryloyl.”

[0031] In this specification, “n-” means normal, “i-” means iso, “s-” means secondary, and “t-” means tertiary.

[0032] In this specification, "adhesive composition" refers to a liquid or paste-like substance before the crosslinking reaction is completed.

[0033] In this specification, "adhesive layer" refers to a film formed from a material after the cross-linking reaction in the adhesive composition has been completed.

[0034] In this specification, "excellent bendability" means having excellent properties that can suppress defects such as whitening that may occur when the unfolded state and the folded state of the foldable display are repeated.

[0035] [Adhesive composition for foldable displays]

[0036] The adhesive composition for a foldable display according to the present invention (hereinafter also referred to simply as "adhesive composition") comprises a (meth)acrylic copolymer [hereinafter also referred to as "specific (meth)acrylic copolymer") comprising a constituent unit derived from a monomer having a hydroxyl group and a constituent unit derived from a (meth)acrylic acid alkyl ester monomer, and a crosslinking agent, wherein when an adhesive layer is formed, the storage modulus at -20°C is in the range of 0.05 MPa or more and 0.5 MPa or less, the ratio of the storage modulus at -20°C to the storage modulus at 100°C is 15.0 or less, and the gel fraction is 50 mass% or more.

[0037] In the present invention, by focusing on the low-temperature storage modulus of the adhesive layer formed by the adhesive composition, the ratio of the low-temperature storage modulus to the high-temperature storage modulus, and the gel fraction, an adhesive composition is realized that can improve thermal shock resistance in a folded state, bendability in a low-temperature environment, and adhesive strength.

[0038] According to the adhesive composition of the present invention, an adhesive layer is formed by the hydroxyl group in a specific (meth)acrylic copolymer, that is, the hydroxyl group of a constituent unit derived from a monomer having a hydroxyl group, reacting with a crosslinking agent to form a crosslinked structure.

[0039] The adhesive composition of the present invention comprises a specific (meth)acrylic copolymer having a constituent unit derived from a monomer having a hydroxyl group and a crosslinking agent, and when an adhesive layer is formed, the storage modulus at low temperature is within a specific range, the ratio of the storage modulus at low temperature to the storage modulus at high temperature is less than or equal to a specific value, and the gel fraction is greater than or equal to a specific value, thereby enabling the formation of an adhesive layer that exhibits excellent thermal shock resistance and bendability in a low-temperature environment when the foldable display is folded, and also exhibits good adhesive strength.

[0040] Storage Modulus

[0041] When an adhesive layer is formed, the adhesive composition of the present invention has a storage modulus at -20°C in the range of 0.05 MPa or more and 0.5 MPa or less, and the ratio of the storage modulus at -20°C to the storage modulus at 100°C is 15.0 or less.

[0042] If the storage modulus of the formed adhesive layer is controlled to satisfy the above requirements, it tends to improve thermal shock resistance in the folded state, as well as bendability and adhesion in low-temperature environments.

[0043] When an adhesive layer is formed, the adhesive composition of the present invention has a storage modulus at -20°C in the range of 0.05 MPa or more and 0.5 MPa or less, preferably in the range of 0.1 MPa or more and 0.45 MPa or less, more preferably in the range of 0.13 MPa or more and 0.35 MPa or less, and even more preferably in the range of 0.13 MPa or more and 0.25 MPa or less.

[0044] Adhesive layers with a storage modulus of 0.05 MPa or higher at -20℃ tend to exhibit good adhesive strength.

[0045] An adhesive layer with a storage modulus of 0.5 MPa or less at -20℃ tends to have excellent bending resistance in low-temperature environments.

[0046] When an adhesive composition of the present invention forms an adhesive layer, the ratio of the storage modulus at -20°C to the storage modulus at 100°C (i.e., storage modulus at -20°C / storage modulus at 100°C) is 15.0 or less, preferably in the range of 4.5 or more and 15.0 or less, more preferably in the range of 4.5 or more and 11.5 or less, and even more preferably in the range of 5.0 or more and 10.0 or less.

[0047] An adhesive layer having a ratio of the storage modulus at -20°C to the storage modulus at 100°C of 15.0 or less tends to have excellent thermal shock resistance when folded.

[0048] In the adhesive composition of the present invention, when an adhesive layer is formed, the storage modulus at 100°C is preferably in the range of 0.01 MPa or more and 0.1 MPa or less, more preferably in the range of 0.012 MPa or more and 0.1 MPa or less, and even more preferably in the range of 0.013 MPa or more and 0.1 MPa or less.

[0049] An adhesive layer having a storage modulus at 100°C within the above range tends to have better thermal shock resistance when folded.

[0050] In this specification, the storage modulus of the adhesive layer is a value measured by the following method.

[0051] As a measuring device, a dynamic viscoelasticity measuring device is used to measure the viscoelasticity spectrum of an adhesive layer with a thickness of 500 μm using the dynamic viscoelasticity measuring method in accordance with JIS K7244-1:1998 (temperature range: -50℃~200℃, heating rate: 10℃ / min, frequency: 1Hz, cone used: 8mmφ) to obtain the storage modulus (G') at -20℃ and 100℃.

[0052] The dynamic viscoelasticity measuring device is not particularly limited, and, for example, Anton Paar’s Physica MCR301 (trademark) may be suitably used. However, the dynamic viscoelasticity measuring device is not limited to this.

[0053] The storage modulus of the adhesive layer can be set to a desired value by, for example, adjusting the monomer composition of the copolymer included in the adhesive composition, the type and content of the crosslinking agent, and the presence, type, and content of additives.

[0054] Hereinafter, each component of the adhesive composition of the present invention will be described in detail.

[0055] [(Meta)acrylic copolymer]

[0056] The adhesive composition of the present invention comprises a (meth)acrylic copolymer [i.e., a specific (meth)acrylic copolymer] comprising a constituent unit derived from a monomer having a hydroxyl group and a constituent unit derived from a (meth)acrylic acid alkyl ester monomer.

[0057] <Constituent units derived from monomers containing hydroxyl groups>

[0058] Certain (meth)acrylic copolymers contain constituent units derived from monomers having hydroxyl groups.

[0059] In the adhesive composition of the present invention, an adhesive layer is formed by the reaction of a hydroxyl group of a constituent unit derived from a monomer having a hydroxyl group included in a specific (meth)acrylic copolymer with a crosslinking agent described below to form a crosslinked structure.

[0060] If a specific (meth)acrylic copolymer includes constituent units derived from monomers having hydroxyl groups, it tends to form an adhesive layer with excellent bending resistance under low-temperature environments.

[0061] In this specification, "constituent unit derived from a monomer having a hydroxyl group" means a constituent unit formed by the addition polymerization of a monomer having a hydroxyl group.

[0062] The types of monomers having hydroxyl groups are not particularly limited.

[0063] Specific examples of monomers having hydroxyl groups include 2-hydroxymethyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 3-hydroxypropyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 10-hydroxydecyl(meth)acrylate, 12-hydroxylauryl(meth)acrylate, 3-methyl-3-hydroxybutyl(meth)acrylate, 1,1-dimethyl-3-hydroxybutyl(meth)acrylate, and 1,3-dimethyl-3-hydroxybutyl(meth)acrylate. Examples include 2,2,4-trimethyl-3-hydroxypentyl(meth)acrylate, 2-ethyl-3-hydroxyhexyl(meth)acrylate, and N-hydroxyethyl(meth)acrylamide.

[0064] As a monomer having a hydroxyl group, hydroxyalkyl (meth)acrylate is preferred in terms of good copolymerization with, for example, the (meth)acrylate alkyl ester monomer described later, hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 1 to 5 carbon atoms is more preferred, and hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms is even more preferred.

[0065] Certain (meth)acrylic copolymers may contain only one type of constituent unit derived from a monomer having a hydroxyl group, or may contain two or more types.

[0066] The content of constituent units derived from monomers having hydroxyl groups in a specific (meth)acrylic copolymer is not particularly limited, but, for example, it is preferably in the range of 1 mass% or more and 15 mass% or less with respect to the total constituent units of the specific (meth)acrylic copolymer, more preferably in the range of 2 mass% or more and 10 mass% or less, and even more preferably in the range of 3 mass% or more and 8 mass% or less.

[0067] If the content of constituent units derived from monomers having hydroxyl groups in a specific (meth)acrylic copolymer is 1 mass% or more relative to the total constituent units of the specific (meth)acrylic copolymer, there is a tendency to form an adhesive layer with superior adhesive strength.

[0068] If the content of constituent units derived from monomers having hydroxyl groups in a specific (meth)acrylic copolymer is 15 mass% or less relative to the total constituent units of the specific (meth)acrylic copolymer, there is a tendency to form an adhesive layer with better bending resistance in a low-temperature environment.

[0069] <Constituent unit derived from (meth)acrylate alkyl ester monomers>

[0070] Certain (meth)acrylic copolymers contain constituent units derived from (meth)acrylate alkyl ester monomers.

[0071] Constituent units derived from (meth)acrylate alkyl ester monomers contribute to the adjustment of adhesive strength.

[0072] In this specification, “constituent unit derived from (meth)acrylate alkyl ester monomer” means a constituent unit formed by addition polymerization of (meth)acrylate alkyl ester monomer.

[0073] Also, the term “(meth)acrylate alkyl ester monomer” in this specification does not include (meth)acrylate alkyl ester monomers having at least one of a hydroxyl group and a carboxyl group.

[0074] As for the (meth)acrylate alkyl ester monomer, an unsubstituted (meth)acrylate alkyl ester monomer is preferred.

[0075] The alkyl group of the (meth)acrylate alkyl ester monomer may be straight, branched, or cyclic.

[0076] For example, the number of carbon atoms in the alkyl group is preferably 1 to 18 in terms of adhesive strength, and more preferably 1 to 12.

[0077] Specific examples of (meth)acrylate alkyl ester monomers include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, i-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, i-nonyl (meth)acrylate, n-decyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate.

[0078] As for the (meth)acrylate alkyl ester monomer, it is preferable to include at least one monomer selected from the group consisting of 2-ethylhexyl acrylate, i-octyl acrylate, and methyl acrylate, for example, in order to make it easy to prepare an adhesive composition exhibiting the aforementioned storage modulus when an adhesive layer is formed; it is more preferable to include at least one monomer selected from the group consisting of 2-ethylhexyl acrylate and i-octyl acrylate; it is even more preferable to include 2-ethylhexyl acrylate or i-octyl acrylate; and it is particularly preferable to include 2-ethylhexyl acrylate.

[0079] Certain (meth)acrylic copolymers may contain only one type of constituent unit derived from (meth)acrylate alkyl ester monomers, or may contain two or more types.

[0080] The content of constituent units derived from (meth)acrylate alkyl ester monomers in a specific (meth)acrylic copolymer is not particularly limited, but, for example, it is preferable to be 50 mass% or more with respect to the total constituent units of the specific (meth)acrylic copolymer, more preferable to be in the range of 50 mass% or more and 99 mass% or less, even more preferable to be in the range of 60 mass% or more and 98 mass% or less, and particularly preferable to be in the range of 70 mass% or more and 97 mass% or less.

[0081] Here, the content of a constituent unit derived from an alkyl ester monomer in a specific (meth)acrylic copolymer is 50 mass% or more relative to the total constituent unit of the specific (meth)acrylic copolymer means that the constituent unit derived from an alkyl ester monomer is included as a main component of the constituent unit constituting the specific (meth)acrylic copolymer.

[0082] <Constituent unit derived from a monomer having a carboxyl group>

[0083] It is desirable that certain (meth)acrylic copolymers include constituent units derived from monomers having carboxyl groups.

[0084] The carboxyl groups of constituent units derived from monomers having carboxyl groups rapidly crosslink with the isocyanate groups of isocyanate-based crosslinking agents. For this reason, when the crosslinking agent included in the present invention is an isocyanate-based crosslinking agent, if a specific (meth)acrylic copolymer contains constituent units derived from monomers having carboxyl groups, the crosslinking reaction proceeds rapidly, and workability tends to be improved.

[0085] When a specific (meth)acrylic copolymer includes a constituent unit derived from a monomer having a carboxyl group in addition to a constituent unit derived from a monomer having a hydroxyl group, it tends to form an adhesive layer exhibiting better adhesive strength.

[0086] In this specification, "constituent unit derived from a monomer having a carboxyl group" means a constituent unit formed by the addition polymerization of a monomer having a carboxyl group.

[0087] The types of monomers having a carboxyl group are not particularly limited.

[0088] Specific examples of monomers having a carboxyl group include acrylic acid (AA), methacrylic acid (MAA), crotonic acid, maleic anhydride, fumaric acid, itaconic acid, glutaconic acid, citraconic acid, ω-carboxy-polycaprolactone mono(meth)acrylate (e.g., ω-carboxy-polycaprolactone (n≒2) monoacrylate) and succinic acid ester (e.g., 2-acryloyloxyethyl-succinic acid).

[0089] As a monomer having a carboxyl group, acrylic acid (AA) is preferred, for example, in the case where the crosslinking agent included in the present invention is an isocyanate-based crosslinking agent, from the view that it has good reactivity with the isocyanate-based crosslinking agent.

[0090] When a specific (meth)acrylic copolymer contains a constituent unit derived from a monomer having a carboxyl group, it may contain only one type of constituent unit derived from a monomer having a carboxyl group, or it may contain two or more types.

[0091] When a specific (meth)acrylic copolymer comprises a constituent unit derived from a monomer having a carboxyl group, the content of the constituent unit derived from a monomer having a carboxyl group in the specific (meth)acrylic copolymer is not particularly limited, but, for example, it is preferably in the range of 0.5 mass% or more and 5 mass% or less with respect to the total constituent unit of the specific (meth)acrylic copolymer, more preferably in the range of 0.5 mass% or more and 3 mass% or less, and even more preferably in the range of 1 mass% or more and 3 mass% or less.

[0092] If the content of constituent units derived from monomers having carboxyl groups in a specific (meth)acrylic copolymer is 0.5 mass% or more relative to the total constituent units of the specific (meth)acrylic copolymer, there is a tendency to form an adhesive layer that exhibits better adhesive strength.

[0093] If the content of constituent units derived from monomers having carboxyl groups in a specific (meth)acrylic copolymer is 5 mass% or less relative to the total constituent units of the specific (meth)acrylic copolymer, there is a tendency to form an adhesive layer with better bending resistance in a low-temperature environment.

[0094] Other constituent units

[0095] Certain (meth)acrylic copolymers may include constituent units other than the aforementioned constituent units (so-called other constituent units) within the scope in which the effects of the present invention are exhibited.

[0096] Examples of monomers constituting other constituent units include (meth)acrylates having an aromatic ring, represented by benzyl (meth)acrylate and phenoxyethyl (meth)acrylate; alkoxyalkyl (meth)acrylates, represented by methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; aromatic monovinyls, represented by styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene, and vinyltoluene; vinyl cyanide, represented by acrylonitrile and methacrylonitrile; and vinyl esters, represented by vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate. In addition, various derivatives of these monomers may be cited.

[0097] Glass Transition Temperature of Specific (Meta)Acrylic Copolymers

[0098] The glass transition temperature (also called "Tg") of a specific (meth)acrylic copolymer is preferably less than -50°C, more preferably in the range of -75°C or higher and less than -50°C, even more preferably in the range of -70°C or higher and less than -50°C, and particularly preferably in the range of -70°C or higher and less than -55°C.

[0099] If the glass transition temperature of a specific (meth)acrylic copolymer is below -50℃, it tends to form an adhesive layer with better bending resistance in low-temperature environments.

[0100] The glass transition temperature of a specific (meth)acrylic copolymer is a value obtained by converting the absolute temperature (unit: K; hereinafter the same) calculated from Formula 1 below into a Celsius temperature (unit: °C; hereinafter the same).

[0101] 1 / Tg=m1 / Tg1+m2 / Tg2+… +m(k-1) / Tg(k-1)+mk / Tgk (Equation 1)

[0102] In Equation 1, Tg1, Tg2, …, Tg(k-1), and Tgk each represent the glass transition temperature expressed as the absolute temperature when each monomer constituting a specific (meth)acrylic copolymer is used as a homopolymer. m1, m2, …, m(k-1), and mk each represent the mole fraction of each monomer constituting a specific (meth)acrylic copolymer, and m1+m2+… +m(k-1)+mk=1.

[0103] Also, absolute temperature can be converted to Celsius temperature by subtracting 273 from absolute temperature, and Celsius temperature can be converted to absolute temperature by adding 273 to Celsius temperature.

[0104] In this specification, "glass transition temperature appearing as an absolute temperature when made into a homopolymer" refers to the glass transition temperature appearing as an absolute temperature of a homopolymer prepared by polymerizing the monomer alone.

[0105] The glass transition temperature of the homopolymer was determined by using a differential scanning calorimeter (DSC) [Model No.: EXSTAR6000, Seiko Instruments, Inc.] to measure 10 mg of the sample in a nitrogen stream under the condition of a heating rate of 10°C / min, and taking the inflection point of the DSC curve as the glass transition temperature of the homopolymer.

[0106] The "glass transition temperatures in degrees Celsius when formed as homopolymers" of representative monomers are -76°C for 2-ethylhexyl acrylate (2EHA), -10°C for 2-ethylhexyl methacrylate (2EHMA), -57°C for n-butyl acrylate (n-BA), 21°C for n-butyl methacrylate (n-BMA), 41°C for t-butyl acrylate (t-BA), 107°C for t-butyl methacrylate (t-BMA), 48°C for i-butyl methacrylate (i-BMA), 5°C for methyl acrylate (MA), 103°C for methyl methacrylate (MMA), 155°C for isobornyl methacrylate (IBXMA), and 96°C for isobornyl acrylate (IBXA). Ethyl acrylate (EA) is -27°C, methacrylic acid (MAA) is 185°C, 4-hydroxybutyl acrylate (4HBA) is -39°C, 2-hydroxyethyl acrylate (2HEA) is -15°C, 2-hydroxyethyl methacrylate (2HEMA) is 55°C, acrylic acid (AA) is 163°C, i-octyl acrylate (i-OA) is -75°C, dimethylaminoethyl methacrylate (DM) is 18°C, ω-carboxy-polycaprolactone (n≒2) monoacrylate is -30°C, and 2-acryloyloxyethyl-succinic acid is -40°C.

[0107] The glass transition temperature of a specific (meth)acrylic copolymer can be appropriately adjusted by using two or more monomers with different glass transition temperatures, for example, when used as a homopolymer.

[0108] <<Weight Average Molecular Weight of Specific (Meta)Acrylic Copolymers>>

[0109] The weight average molecular weight (also called "Mw") of a specific (meth)acrylic copolymer is preferably 800,000 or more, more preferably 900,000 or more, even more preferably 1,000,000 or more, and particularly preferably 1,300,000 or more.

[0110] If the weight average molecular weight of a specific (meth)acrylic copolymer is 800,000 or more, it tends to form an adhesive layer with better thermal shock resistance in a folded state.

[0111] In addition, the weight average molecular weight of a specific (meth)acrylic copolymer is preferably 2 million or less, more preferably 1.8 million or less, and even more preferably 1.65 million or less.

[0112] If the weight average molecular weight of a specific (meth)acrylic copolymer is 2 million or less, it tends to form an adhesive layer with better bending resistance under low-temperature environments.

[0113] The weight-average molecular weight of a specific (meth)acrylic copolymer is a value measured by the following method. Specifically, it is measured according to (1) to (3) below.

[0114] (1) A solution of a specific (meth)acrylic copolymer is applied to a release liner and dried at 100°C for 1 minute to obtain a film-shaped specific (meth)acrylic copolymer.

[0115] (2) A sample solution with a solid content concentration of 0.2 mass% is obtained by using the specific (meth)acrylic copolymer in film form obtained in (1) above and tetrahydrofuran. Also, the term “solid content concentration” here refers to the mass ratio of the specific (meth)acrylic copolymer in the sample solution.

[0116] (3) The weight average molecular weight of a specific (meth)acrylic copolymer is measured as a standard polystyrene equivalent value using gel permeation chromatography (GPC) under the following conditions.

[0117] ~condition~

[0118] Measuring device: High-speed GPC [Model number: HLC-8220 GPC, Tosoh Corporation]

[0119] Detector: Differential Refractive Index (RI) [Incorporated into HLC-8220, Tosoh Corp.]

[0120] Column: 4 TSK-GEL GMHXL [Toso Corp.] units connected in series

[0121] Column temperature: 40℃

[0122] Eluent: Tetrahydrofuran

[0123] Sample solution injection volume: 100μL

[0124] Flow rate: 0.8 mL / min

[0125] The weight-average molecular weight of a specific (meth)acrylic copolymer can be set to a desired value by adjusting the polymerization temperature, polymerization time, amount of organic solvent, type of polymerization initiator, amount of polymerization initiator, etc.

[0126] <<Content of Specific (Meta)Acrylic Copolymer>>

[0127] The content of a specific (meth)acrylic copolymer in the adhesive composition of the present invention is not particularly limited, but, for example, in terms of reactivity with a crosslinking agent, it is preferable to be in the range of 80 mass% or more and 99.9 mass% or less with respect to the total solid content in the adhesive composition, more preferable to be in the range of 85 mass% or more and 99.9 mass% or less, even more preferable to be in the range of 90 mass% or more and 99.9 mass% or less, and particularly preferable to be in the range of 95 mass% or more and 99.9 mass% or less.

[0128] In this specification, "total solid content in the adhesive composition" refers to the total mass of the adhesive composition when the adhesive composition does not contain a solvent, and refers to the mass of the residue excluding the solvent from the adhesive composition when the adhesive composition contains a solvent.

[0129] In this specification, "solvent" means water and organic solvents.

[0130] [Method for manufacturing a specific (meth)acrylic copolymer]

[0131] The method of manufacturing a specific (meth)acrylic copolymer is not particularly limited.

[0132] Certain (meth)acrylic copolymers can be produced by polymerizing the aforementioned monomers using known polymerization methods, such as solution polymerization, emulsion polymerization, suspension polymerization, and bulk polymerization.

[0133] As for the polymerization method, the solution polymerization method is preferred in that the processing step for preparing the adhesive composition of the present invention after manufacturing is relatively simple and can be carried out in a short time.

[0134] In the solution polymerization method, a specified organic solvent, monomer, polymerization initiator, and a chain transfer agent used as needed are generally placed in a polymerization vessel, and the reaction is heated for several hours under a nitrogen stream while stirring at the reflux temperature of the organic solvent. In this case, at least a portion of the organic solvent, monomer, polymerization initiator, and / or chain transfer agent may be added sequentially.

[0135] Organic solvents used in polymerization reactions include aromatic hydrocarbon compounds, aliphatic or alicyclic hydrocarbon compounds, ester compounds, ketone compounds, glycol ether compounds, alcohol compounds, etc.

[0136] As organic solvents used in polymerization reactions, more specifically, examples include aromatic hydrocarbon compounds represented by benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; aliphatic or alicyclic hydrocarbon compounds represented by n-hexane, n-heptane, n-octane, i-octane, n-decane, dipentene, petroleum spirits, petroleum naphtha, and turpentine oils; ester compounds represented by ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate; acetone, methyl ethyl ketone, methyl-i-butyl ketone, isophorone, cyclohexanone, and Examples include ketone compounds represented by methylcyclohexanone, glycol ether compounds represented by ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether, and alcohol compounds represented by methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, s-butyl alcohol, and t-butyl alcohol.

[0137] When manufacturing a specific (meth)acrylic copolymer, it is desirable to use an organic solvent that is difficult to cause chain transfer during the polymerization reaction, such as aromatic hydrocarbon compounds, ester compounds, and ketone compounds, and in particular, it is desirable to use ethyl acetate from the perspective of the solubility of the specific (meth)acrylic copolymer and the ease of the polymerization reaction.

[0138] In the polymerization reaction, only one type of organic solvent may be used, or two or more types may be used.

[0139] Examples of polymerization initiators include organic peroxides and azo compounds used in conventional solution polymerization methods.

[0140] Organic peroxides include, for example, t-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, caproyl peroxide, di-i-propyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-butyl peroxypivalate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)butane and Examples include 2,2-bis(4,4-di-t-octylperoxycyclohexyl)butane.

[0141] Examples of azo compounds include 2,2'-azobis(isobutyronitrile) [AIBN], 2,2'-azobis(2,4-dimethylvaleronitrile) [ABVN], 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(isobutyric acid)dimethyl.

[0142] When manufacturing certain (meth)acrylic copolymers, it is desirable to use a polymerization initiator that does not cause a graft reaction during the polymerization reaction, and in particular, it is desirable to use an azo compound.

[0143] In the polymerization reaction, only one type of polymerization initiator may be used, or two or more types may be used.

[0144] The amount of polymerization initiator used is not particularly limited and can be appropriately set according to, for example, the molecular weight of the specific (meth)acrylic copolymer intended for use.

[0145] When manufacturing certain (meth)acrylic copolymers, a chain transfer agent may be used as needed.

[0146] As chain transfer agents, examples include cyanoacetic acid, alkyl ester compounds of cyanoacetic acid having 1 to 8 carbon atoms, bromoacetic acid, alkyl ester compounds of bromoacetic acid having 1 to 8 carbon atoms, aromatic compounds represented by α-methylstyrene, anthracene, phenanthrene, fluorene, and 9-phenylfluorene, aromatic nitro compounds represented by p-nitroaniline, nitrobenzene, dinitrobenzene, p-nitrobenzoic acid, p-nitrophenol, and p-nitrotoluene, benzoquinone derivatives represented by benzoquinone and 2,3,5,6-tetramethyl-p-benzoquinone, borane derivatives represented by tributylborane, carbon tetrabromide, carbon tetrachloride, 1,1,2,2-tetrabromoethane, tribromoethylene, trichloroethylene, bromotrichloromethane, tribromomethane, and Examples include halogenated hydrocarbon compounds represented by 3-chloro-1-propene, aldehyde compounds represented by chloral and furaldehyde, alkyl mercaptan compounds having 1 to 18 carbon atoms, aromatic mercaptan compounds represented by thiophenol and toluene mercaptan, mercaptoacetic acid, alkyl ester compounds of mercaptoacetic acid having 1 to 10 carbon atoms, hydroxyalkyl mercaptan compounds having 1 to 12 carbon atoms, and terpene compounds represented by pinene and terpinolene.

[0147] When a chain transfer agent is used in the manufacture of a specific (meth)acrylic copolymer, the amount of chain transfer agent used is not particularly limited and can be appropriately set, for example, according to the molecular weight of the specific (meth)acrylic copolymer to be targeted.

[0148] The polymerization temperature is not specifically limited and can be appropriately set, for example, according to the molecular weight of the specific (meth)acrylic copolymer intended for the purpose.

[0149] [Crosslinking agent]

[0150] The adhesive composition of the present invention includes a crosslinking agent.

[0151] The type of crosslinking agent is not particularly limited.

[0152] Examples of crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and metal chelate-based crosslinking agents.

[0153] In this specification, "isocyanate-based crosslinking agent" refers to a compound having two or more isocyanate groups in a molecule (so-called polyisocyanate compounds). Also, "epoxy-based crosslinking agent" refers to a compound having two or more epoxy groups in a molecule (so-called difunctional or higher epoxy compounds). Also, "metal chelate-based crosslinking agent" refers to a metal chelate compound that functions as a crosslinking agent (hereinafter also referred to simply as "metal chelate compounds").

[0154] Examples of polyisocyanate compounds include aromatic polyisocyanate compounds such as xylylene diisocyanate (XDI), diphenylmethane diisocyanate, triphenylmethane triisocyanate, and tolylene diisocyanate (TDI), aliphatic or alicyclic polyisocyanate compounds such as hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate, and hydrogenated aromatic polyisocyanate compounds.

[0155] In addition, examples of polyisocyanate compounds include dimers, trimers, or pentamers of the polyisocyanate compound, adducts of the polyisocyanate compound and polyol compounds such as trimethylolpropane, and biurets of the polyisocyanate compound.

[0156] Commercially available products can be used as isocyanate-based crosslinking agents.

[0157] Examples of commercially available isocyanate-based crosslinking agents include “Colonate (Registered Trademark) HX”, “Colonate (Registered Trademark) HL-S”, “Colonate (Registered Trademark) L”, “Colonate (Registered Trademark) L-45E”, “Colonate (Registered Trademark) 2031”, “Colonate (Registered Trademark) 2030”, “Colonate (Registered Trademark) 2234”, “Colonate (Registered Trademark) 2785”, “Aquanate (Registered Trademark) 200” and “Aquanate (Registered Trademark) 210” [all from Tosoh Corporation], “Smidul (Registered Trademark) N3300”, “Desmodul (Registered Trademark) N3400” and “Smidul (Registered Trademark) N-75” [all from Sumika Covestro Urethane Co., Ltd.], Examples include “Duranate (registered trademark) E-405-80T”, “Duranate (registered trademark) AE700-100”, “Duranate (registered trademark) 24A-100” and “Duranate (registered trademark) TSE-100” [all from Asahi Kasei Co., Ltd.], “Takenate (registered trademark) D-110N”, “Takenate (registered trademark) D-120N”, “Takenate (registered trademark) M-631N”, “MT-Olester (registered trademark) NP1200” and “Stavio (registered trademark) XD-340N” [all from Mitsui Chemicals Co., Ltd.].

[0158] Examples of epoxy compounds with two or more functions include ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, resorcinol diglycidyl ether, 2,2-dibromoneopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol polyglycidyl ether, sorbitol polyglycidyl ether, adipic acid diglycidyl ester, and phthalic acid Examples include diglycidyl esters, tris(glycidyl) isocyanurate, tris(glycidoxyethyl) isocyanurate, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane and N,N,N',N'-tetraglycidyl-1,3-benzene di(methaneamine).

[0159] Commercially available products can be used as epoxy-based crosslinking agents.

[0160] Examples of commercially available epoxy-based crosslinking agents include “TETRAD (registered trademark)-X” and “TETRAD (registered trademark)-C” [both from Mitsubishi Gas Chemical Co., Ltd.].

[0161] Examples of metal chelate compounds include aluminum chelate compounds represented by aluminum monoacetylacetonate bis(ethylacetoacetate), aluminum tris(ethylacetoacetate), and aluminum tris(acetylacetonate), titanium chelate compounds, zirconium chelate compounds, and cobalt chelate compounds.

[0162] Commercially available products can be used as metal chelate-based crosslinking agents.

[0163] Examples of commercially available metal chelate-based crosslinking agents include "Alumichelate A," "Alumichelate D," and "ALCH-TR" [all from Kawaken Fine Chemical Co., Ltd.].

[0164] As a crosslinking agent, an isocyanate-based crosslinking agent is preferred. In addition, hexamethylene diisocyanate (HMDI) is preferred as an isocyanate-based crosslinking agent.

[0165] The adhesive composition of the present invention tends to form an adhesive layer with better bending resistance under low-temperature environments when it includes hexamethylene diisocyanate (HMDI), an isocyanate-based crosslinking agent, as a crosslinking agent.

[0166] The adhesive composition of the present invention may include only one type of crosslinking agent or two or more types.

[0167] The content of the crosslinking agent in the adhesive composition of the present invention is not particularly limited and is appropriately set, for example, depending on the type of crosslinking agent.

[0168] For example, when the adhesive composition of the present invention includes an isocyanate-based crosslinking agent as a crosslinking agent, the content of the isocyanate-based crosslinking agent in the adhesive composition is preferably in the range of 0.1 parts by mass or more and 5 parts by mass or less per 100 parts by mass of a specific (meth)acrylic copolymer, more preferably in the range of 0.1 parts by mass or more and 3 parts by mass or less, and even more preferably in the range of 0.1 parts by mass or more and 1 part by mass or less.

[0169] If the content of the isocyanate-based crosslinking agent in the adhesive composition of the present invention is 0.1 parts by mass or more per 100 parts by mass of a specific (meth)acrylic copolymer, there is a tendency to form an adhesive layer with better thermal shock resistance in a folded state.

[0170] If the content of the isocyanate-based crosslinking agent in the adhesive composition of the present invention is 5 parts by mass or less per 100 parts by mass of a specific (meth)acrylic copolymer, there is a tendency to form an adhesive layer exhibiting better adhesive strength. In addition, there is a tendency to form an adhesive layer with better bending resistance under low-temperature environments.

[0171] [Adhesion-importing agent]

[0172] The adhesive composition of the present invention may further include an adhesion promoter.

[0173] If the adhesive composition of the present invention further includes a tackifier, it tends to form an adhesive layer exhibiting better adhesive strength.

[0174] Tackifiers are not particularly limited and examples include terpene phenol resin, aromatic modified terpene resin, and styrene resin.

[0175] Among these, terpene phenol resin is preferred as a tackifier.

[0176] Terpene phenol resin is a copolymer of terpene compounds and phenol compounds.

[0177] Examples of terpene phenol resins include copolymers of monocyclic monoterpene compounds represented by α-pinene, β-pinene, and dipentene (limonene), and phenol compounds represented by phenol, cresol, and bisphenol A.

[0178] Commercial products can be used as terpene phenol resins that act as tackifiers.

[0179] Examples of commercially available terpene phenol resins that act as tackifiers include, for instance, "YS Polystar U115," "YS Polystar U130," "YS Polystar T80," "YS Polystar T100," "YS Polystar T115," "YS Polystar T130," "YS Polystar TH130," "YS Polystar T145," "YS Polystar T160," "YS Polystar S145," "YS Polystar G125," "YS Polystar G150," "YS Polystar N125," "YS Polystar K125," and "YS Polystar K140" from Yasuhara Chemical Co., Ltd., and "Tamanol 803L" and "Tamanol 901" from Arakawa Chemical Industry Co., Ltd. (all are product names).

[0180] When the adhesive composition of the present invention includes a tackifier, it may include only one type of tackifier or two or more types.

[0181] When the adhesive composition of the present invention includes a tackifier, the content of the tackifier in the adhesive composition is not particularly limited, but for example, from the perspective of improving adhesive strength, it is preferable that the range is 5 parts by mass or more and 25 parts by mass or less per 100 parts by mass of a specific (meth)acrylic copolymer, more preferable that the range is 10 parts by mass or more and 25 parts by mass or less, and even more preferable that the range is 15 parts by mass or more and 25 parts by mass or less.

[0182] [Organic Solvents]

[0183] The adhesive composition of the present invention may include an organic solvent, for example, for the purpose of improving applicability.

[0184] Examples of organic solvents include the organic solvent used in the polymerization reaction of the aforementioned specific (meth)acrylic copolymer.

[0185] When the adhesive composition of the present invention includes an organic solvent, it may include only one type of organic solvent or two or more types.

[0186] When the adhesive composition of the present invention includes an organic solvent, the content of the organic solvent is not particularly limited and can be appropriately set according to the purpose.

[0187] [Other ingredients]

[0188] The adhesive composition of the present invention may include, if necessary, components other than the aforementioned components (so-called other components) to a extent that does not impair the effects of the present invention.

[0189] Examples of other components include polymers other than specific (meth)acrylic copolymers, crosslinking catalysts, antioxidants, coloring agents (e.g., dyes and pigments), and light stabilizers (e.g., ultraviolet absorbers).

[0190] For example, since a (meth)acrylic polymer with a weight average molecular weight of 30,000 or less can function as a tackifier, if the adhesive composition of the present invention includes the (meth)acrylic polymer, the adhesive strength of the formed adhesive layer can be further improved.

[0191] If the adhesive composition of the present invention includes other components, the content of the other components can be appropriately set within the range in which the effects of the present invention are exhibited.

[0192] Gel fraction after crosslinking

[0193] In the adhesive composition of the present invention, when an adhesive layer is formed, the gel fraction (so-called gel fraction after crosslinking of the adhesive composition) is preferably 50 mass% or more, in the range of 50 mass% or more and 90 mass% or less, more preferably in the range of 55 mass% or more and 80 mass% or less, and even more preferably in the range of 68 mass% or more and 75 mass% or less.

[0194] If the gel fraction after crosslinking of the adhesive composition is 50 mass% or more, there is a tendency to form an adhesive layer with excellent thermal shock resistance in a folded state.

[0195] In this specification, “gel fraction after crosslinking of the adhesive composition” is the ratio of solvent-insoluble matter measured using ethyl acetate as an extraction solvent. Specifically, the gel fraction after crosslinking of the adhesive composition is measured according to (1) to (4) below.

[0196] (1) About 0.15 g of the adhesive composition (i.e., adhesive layer) after crosslinking is attached to a 250 mesh wire mesh (100 mm × 100 mm) whose mass is accurately measured using a precision balance. The wire mesh is folded 5 times with the attached adhesive layer facing inward to prevent leakage of the gel, and the mass is then accurately measured using a precision balance.

[0197] (2) Immerse the obtained sample in 80 mL of ethyl acetate for 3 days.

[0198] (3) Take a sample, wash it with a small amount of ethyl acetate, and dry it at 120°C for 24 hours. Then, accurately measure the mass using a precision balance.

[0199] (4) Calculate the gel fraction using the following formula.

[0200] Gel fraction (unit: mass%) = (ZX) / (YX) × ​​100

[0201] Where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the adhesive layer attached before immersion (unit: g), and Z is the mass of the wire mesh with the adhesive layer attached after drying following immersion (unit: g).

[0202] <Uses>

[0203] The adhesive composition of the present invention is suitable for foldable displays.

[0204] Since the adhesive composition of the present invention has excellent thermal shock resistance in a folded state and bendability in a low-temperature environment, and can form an adhesive layer exhibiting good adhesive strength, it is preferable to use it for applications such as bonding a foldable display and an optical member, for example, as this allows the effects of the adhesive composition of the present invention to be more fully realized.

[0205] [Optical component for foldable display]

[0206] The optical member for a foldable display of the present invention (hereinafter also referred to simply as "optical member") comprises an adhesive layer formed by the adhesive composition of the present invention.

[0207] The adhesive layer provided by the optical member of the present invention is an adhesive layer formed by the adhesive composition of the present invention described above. Since it exhibits excellent thermal shock resistance in a folded state and excellent bendability in a low-temperature environment, and also demonstrates good adhesive strength, a foldable display using the optical member of the present invention tends to be less prone to defects such as whitening or breakage of the adhesive layer in the folded portion, even when it is repeatedly folded in a low-temperature environment or exposed to rapid changes in ambient temperature while folded.

[0208] There are no particular restrictions on the optical components, and examples include components constituting devices such as image display devices and input devices (so-called optical devices) or components used in these devices.

[0209] Specific examples of optical members include polarizers, AG (Anti-Glare) polarizers, wave plates, phase difference plates including wave plates of 1 / 2, 1 / 4, etc., visual compensation films, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflective films, transparent conductive films such as ITO (Indium-Tin Oxide) films, prism sheets, lens sheets, and diffusers.

[0210] Examples of materials for optical components include polyester resins (e.g., polyethylene terephthalate), acetate resins (e.g., triacetylcellulose resin), polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins (e.g., polyethylene and polypropylene), acrylic resins, vinyl chloride resins, ABS (Acrylonitrile Butadiene Styrene) resins, fluorine resins, etc.

[0211] The thickness of the adhesive layer in the optical member of the present invention is not particularly limited and can be appropriately set according to, for example, the type of the optical member and the foldable display, the material of the optical member and the foldable display, etc. Generally, the thickness of the adhesive layer is in the range of 1 μm or more and 100 μm or less, and is preferably in the range of 5 μm or more and 50 μm or less, and more preferably in the range of 10 μm or more and 30 μm or less.

[0212] The optical member of the present invention can be manufactured by a known method.

[0213] A known method may be, for example, to apply the adhesive composition of the present invention to the easy-to-peel surface of a release film to form a coating film. Next, the formed coating film is dried to form an adhesive film on the release film. Next, the formed adhesive film is transferred onto an optical member and cured to produce an optical member having an adhesive layer formed by the adhesive composition of the present invention.

[0214] In addition, as another method, for example, the adhesive composition of the present invention is applied to the easy-release treatment surface of a release film to form a coating film. Next, the formed coating film is dried to form an adhesive film on the release film. Next, a double-sided adhesive sheet without a base material is produced by overlapping and bonding the easy-release treatment surface of a release film prepared separately to the exposed surface of the formed adhesive film. Next, the adhesive film of the produced double-sided adhesive sheet is cured to form an adhesive layer. Next, one of the release films is peeled off to transfer the exposed adhesive layer onto an optical member, thereby producing an optical member having an adhesive layer formed by the adhesive composition of the present invention.

[0215] In addition, as another method, for example, the adhesive composition of the present invention is applied onto an optical member to form a coating film. Next, the formed coating film is dried to form an adhesive film on the optical member. Next, the formed adhesive film is cured to produce an optical member of the present invention having an adhesive layer formed by the adhesive composition of the present invention.

[0216] In addition, as a drying condition, for example, a condition of drying at 70°C to 120°C for 1 to 3 minutes using a hot air dryer can be cited.

[0217] Examples

[0218] The present invention will be explained in more detail below by way of examples. The present invention is not limited to the following examples unless it goes beyond the scope of the well-known invention.

[0219] [Preparation of (Meta)Acrylic Copolymers]

[0220] [Preparation Example A-1]

[0221] 84 parts by mass of 2-ethylhexyl acrylate [2EHA; alkyl acrylate monomer, Tg when homopolymerized: -76°C], 10 parts by mass of methyl acrylate [MA; alkyl acrylate monomer, Tg when homopolymerized: 5°C], 5 parts by mass of 2-hydroxyethyl acrylate [2HEA; monomer having a hydroxyl group, Tg when homopolymerized: -15°C], 1 part by mass of acrylic acid [AA; monomer having a carboxyl group, Tg when homopolymerized: 163°C], and 60 parts by mass of ethyl acetate were added and mixed, and then the air in the reactor was replaced with nitrogen gas. Next, while stirring the mixture in the reactor, the temperature of the mixture was raised to 75°C (reflux temperature), and then a mixed solution of 0.02 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) [ABVN; polymerization initiator] and 10 parts by mass of ethyl acetate was sequentially added, and the mixture was maintained for 6 hours after the addition was finished to obtain a polymerization reaction product. The obtained polymerization reaction product was diluted with ethyl acetate to obtain a solution of (meth)acrylic copolymer A-1 with a solid content concentration of 15 mass%.

[0222] The term "solid content concentration" used here refers to the mass ratio of (meth)acrylic copolymer A-1 in the solution of (meth)acrylic copolymer A-1.

[0223] The same applies to each solution of the following (meth)acrylic copolymers A-2 to A-13.

[0224] [Preparation Examples A-2~A-10]

[0225] In Preparation Examples A-2 to A-10, the monomer composition of the (meth)acrylic copolymer was changed to the monomer composition shown in Table 1, and the weight average molecular weight (Mw) of the (meth)acrylic copolymer was adjusted to the weight average molecular weight (Mw) shown in Table 1 by adjusting at least one of the amount of organic solvent and the amount of polymerization initiator, and the same operation as in Preparation Example A-1 was performed to obtain each solution of (meth)acrylic copolymer A-2 to A-10 having a solid content concentration of 15 mass%.

[0226] [Preparation Examples A-11~A-13]

[0227] In Preparation Examples A-11 to A-13, the same operation as in Preparation Example A-1 was performed to obtain each solution of (meth)acrylic copolymer A-11 to A-13 having a solid content concentration of 15 mass%, except that the weight average molecular weight (Mw) of the (meth)acrylic copolymer was adjusted to the weight average molecular weight (Mw) shown in Table 1 by adjusting at least one of the amount of organic solvent and the amount of polymerization initiator.

[0228] [Manufacture of (Meta)Acrylic Polymers]

[0229] [Preparation Example A-14]

[0230] 106 parts by mass of ethyl acetate were placed into a reactor equipped with a thermometer, a stirrer, a reflux condenser, and a sequential dropping device, and then heated to 80°C (reflux temperature) for 10 minutes. Next, while maintaining the temperature inside the reactor at the reflux temperature, a mixed solution of 400 parts by mass of methyl acrylate [MA; alkyl acrylate monomer, Tg when formed as a homopolymer: 5°C], 80.6 parts by mass of ethyl acetate, and 51.4 parts by mass of 2,2'-azobis(isobutyric acid)dimethyl was sequentially added over a period of 180 minutes, and the mixture was maintained for 180 minutes after the addition was finished to obtain a polymerization reaction product. The obtained polymerization reaction product was diluted with ethyl acetate to obtain a solution of (meth)acrylic polymer A-14 having a solid content concentration of 62% by mass.

[0231] The term "solid content concentration" used here refers to the mass ratio of (meth)acrylic polymer A-14 in a solution of (meth)acrylic polymer A-14.

[0232] Monomer composition (unit: mass%), glass transition temperature (Tg) [unit: °C] and weight average molecular weight (Mw) [unit: ten thousand (in the table, ×10 4 [Notated as 」] is shown in Table 1.

[0233] The glass transition temperatures (Tg) of (meth)acrylic copolymers A-1 to A-13 and (meth)acrylic polymer A-14 were calculated by the same method as the calculation method for the glass transition temperatures (Tg) of the specific (meth)acrylic copolymers described above.

[0234] The weight average molecular weight (Mw) of (meth)acrylic copolymers A-1 to A-13 and (meth)acrylic polymer A-14 was measured by the same method as the weight average molecular weight (Mw) of the specific (meth)acrylic copolymer described above.

[0235]

[0236] The details of each monomer listed in Table 1 are as follows.

[0237] Alkyl acrylate ester monomer

[0238] "2EHA": 2-ethylhexyl acrylate [Tg as a homopolymer: -76℃]

[0239] "i-OA": i-octyl acrylate [Tg as a homopolymer: -75℃]

[0240] "MA": Methyl acrylate [Tg when as a homopolymer: 5℃]

[0241] <Monomers having hydroxyl groups>

[0242] "2HEA": 2-hydroxyethyl acrylate [Tg as a homopolymer: -15℃]

[0243] Monomer having a carboxyl group

[0244] "AA": Acrylic acid [Tg as a homopolymer: 163℃]

[0245] In Table 1, "-" indicates that the monomer corresponding to that column is not included.

[0246] In Table 1, the “glass transition temperature (Tg)” is simply labeled “Tg”, and the “weight average molecular weight (Mw)” is simply labeled “Mw”.

[0247] [Preparation of adhesive composition]

[0248] [Example 1]

[0249] The adhesive composition of Example 1 was obtained by thoroughly mixing 100 parts by mass (converted to solid content) of a solution of (meth)acrylic copolymer A-1 and 0.2 parts by mass (converted to solid content) of a crosslinking agent [product name: Smidul (registered trademark) N-75, a biuret-modified hexamethylene diisocyanate compound, an isocyanate-based crosslinking agent, Sumika Covestro Urethane Co., Ltd.].

[0250] [Examples 2–15]

[0251] Each adhesive composition of Examples 2 to 15 was obtained by performing the same operation as in Example 1, except that the composition of the adhesive composition in Example 1 was changed to the composition shown in Table 2.

[0252] [Comparative Examples 1–5]

[0253] Each adhesive composition of Comparative Examples 1 to 5 was obtained by performing the same operation as in Example 1, except that the composition of the adhesive composition in Example 1 was changed to the composition shown in Table 3.

[0254] [Measurement of Gel Fraction]

[0255] The gel fraction (i.e., the gel fraction of the adhesive layer) after crosslinking was measured using each adhesive composition of Examples 1 to 15 and Comparative Examples 1 to 5. Specifically, it was measured by the following method.

[0256] A coating film was formed by applying an adhesive composition to the surface-treated surface of a release film [Product name: Film Biner (Registered Trademark) 100E-0010 No.23, Fujimori Industry Co., Ltd.] so that the thickness after drying was 20 μm.

[0257] Next, the formed coating film was dried using a hot air circulating dryer under drying conditions of a drying temperature of 100°C and a drying time of 1 minute to form an adhesive film on the release film.

[0258] Next, the exposed surface of the adhesive film was overlapped and bonded to the surface treatment surface of a separately prepared release film [Product name: Film Biner (Registered Trademark) 100E-0010 No.23, Fujimori Industry Co., Ltd.], and then cured by allowing the cross-linking reaction to proceed by curing under an environment of an atmosphere temperature of 25°C and 50% RH, thereby producing a baseless type double-sided adhesive sheet having a composition of release film / adhesive layer / release film.

[0259] The gel fraction was measured according to (1) to (4) below using the adhesive layer peeled from the obtained double-sided adhesive sheet. The results are shown in Tables 2 and 3.

[0260] (1) About 0.15 g of adhesive layer is attached to a 250 mesh wire mesh (100 mm × 100 mm) whose mass is accurately measured using a precision balance, and the wire mesh is folded 5 times with the attached adhesive layer facing inward to prevent leakage of the gel powder, and then the mass is accurately measured using a precision balance.

[0261] (2) Immerse the obtained sample in 80 mL of ethyl acetate for 3 days.

[0262] (3) Take a sample, wash it with a small amount of ethyl acetate, and dry it at 120°C for 24 hours. Then, accurately measure the mass using a precision balance.

[0263] (4) Calculate the gel fraction using the following formula.

[0264] Gel fraction (unit: mass%) = (ZX) / (YX) × ​​100

[0265] Where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the adhesive layer attached before immersion (unit: g), and Z is the mass of the wire mesh with the adhesive layer attached after drying following immersion (unit: g).

[0266] [Measurement of Storage Modulus]

[0267] The storage modulus of the adhesive layer was measured using each adhesive composition of Examples 1 to 15 and Comparative Examples 1 to 5. Specifically, it was measured by the following method.

[0268] A coating film was formed by applying an adhesive composition to the surface-treated surface of a release film [Product name: Film Biner (Registered Trademark) 100E-0010 No.23, Fujimori Industry Co., Ltd.] so that the thickness after drying was 20 μm.

[0269] Next, the formed coating film was dried using a hot air circulating dryer under drying conditions of a drying temperature of 100°C and a drying time of 1 minute to form an adhesive film on the release film.

[0270] Next, the exposed surface of the adhesive film was overlapped with the surface-treated surface of a release film [Product Name: Film Biner (Registered Trademark) 100E-0010 No.23, Fujimori Industry Co., Ltd.] which was surface-treated with a silicone-based release agent, and then cured by allowing it to stand for 168 hours in an environment of 25°C and 50% RH to carry out a cross-linking reaction, thereby producing a baseless type double-sided adhesive sheet having a composition of release film / adhesive layer / release film.

[0271] Next, by overlapping the adhesive layers of the baseless type double-sided adhesive sheet produced, an adhesive layer with a thickness of 500 μm was obtained.

[0272] Next, the viscoelastic spectrum of the obtained adhesive layer was measured using a dynamic viscoelasticity measuring device (product name: Physica MCR301) from Anton Paar, according to the dynamic viscoelasticity measurement method in accordance with JIS K7244-1:1998 (temperature range: -50℃ to 200℃, heating rate: 10℃ / min, frequency: 1Hz, cone used: 8mmφ), to determine the storage modulus (G') at -20℃ and 100℃. Then, based on the obtained values, the ratio of the storage modulus at -20℃ to the storage modulus at 100℃ (i.e., storage modulus at -20℃ / storage modulus at 100℃) was calculated. The results are shown in Tables 2 and 3.

[0273] [evaluation]

[0274] The following evaluations were performed on each adhesive composition of Examples 1 to 15 and Comparative Examples 1 to 5. The results are shown in Tables 2 and 3.

[0275] <Preparation of Samples for Evaluation Tests>

[0276] A coating film was formed by applying an adhesive composition to the surface-treated surface of a release film [Product name: Film Biner (Registered Trademark) 100E-0010 No.23, Fujimori Industry Co., Ltd.] so that the thickness after drying was 20 μm.

[0277] Next, the formed coating film was dried using a hot air circulating dryer under drying conditions of a drying temperature of 100°C and a drying time of 1 minute to form an adhesive film on the release film.

[0278] Next, the exposed surface of the adhesive film was overlapped and bonded to a polyethylene terephthalate (PET) film [product name: Teijin Tetron HPE, thickness: 50 μm, Teijin DuPont Corp.], and then cured for 168 hours in an environment with an ambient temperature of 25°C and 50% RH to carry out a cross-linking reaction, thereby producing an evaluation test sample having the composition of a release film / adhesive layer / PET film (hereinafter referred to as "PET with adhesive layer attached").

[0279] 1. Adhesion

[0280] PET with an adhesive layer attached was cut into pieces 25mm × 150mm in size.

[0281] Next, the release film of the PET (composition: release film / adhesive layer / PET film) with the cut adhesive layer attached was peeled off, and the surface of the adhesive layer exposed by peeling was overlapped and attached to the surface of a polyimide (PI) film [product name: Kapton (registered trademark) 100H, Toray-DuPont Corp.] attached to a stainless steel plate (so-called SUS), and then compressed using a 2kg roller to prepare a sample for evaluating adhesive strength. This sample for evaluating adhesive strength was left standing for 24 hours in an environment with an ambient temperature of 25℃ and 50% RH. Next, using a single-column material testing machine (model number: STA-1225) from A&D Co., Ltd. as a measuring device, the adhesive strength (unit: N / 25mm) was measured when a PET film (composition: adhesive layer / PET film) with an adhesive layer attached to it was peeled 180° in the long side (150mm) direction from a PI film under conditions of an ambient temperature of 25℃ and 50% RH and a peeling speed of 300mm / min. Then, the adhesive strength was evaluated according to the following evaluation criteria.

[0282] It was determined that there were no practical problems if the evaluation result was "A," "B," or "C."

[0283] -metewand-

[0284] A: The adhesive strength is 10N / 25mm or greater.

[0285] B: The adhesive strength is 6N / 25mm or greater and less than 10N / 25mm.

[0286] C: The adhesive strength is 3N / 25mm or greater and less than 6N / 25mm.

[0287] D: Adhesion is less than 3N / 25mm.

[0288] 2. Thermal shock resistance in the bent state

[0289] PET with an adhesive layer attached was cut into pieces 25mm × 150mm in size.

[0290] Next, the release film of the PET (composition: release film / adhesive layer / PET film) with the cut adhesive layer attached was peeled off, and the surface of the adhesive layer exposed by peeling was overlapped and attached to the surface of a polyimide (PI) film [product name: Kapton (registered trademark) 100H, Toray-DuPont Corp.] and then compressed using a 2kg roller to make a sample for a bending test (hereinafter referred to as "Sample X").

[0291] Sample X was bent to a radius of curvature (R) of 10 mm. Then, a test was conducted by repeating the operation of placing the bent Sample X in an environment of -20°C for 30 minutes, followed by placing it in an environment of 100°C for 30 minutes, for 200 cycles. Immediately after the test was completed, the bent Sample X was fully unfolded and placed in an environment of 25°C. Then, immediately after placing it in an environment of 25°C (i.e., immediately after the test was completed), 1 hour after placing it, and 24 hours after placing it, the bent portion of Sample X was observed using a magnifying glass, and the thermal shock resistance in the bent state was evaluated according to the following evaluation criteria.

[0292] It was determined that there were no practical problems if the evaluation result was "A," "B," or "C."

[0293] -metewand-

[0294] A: No change was confirmed at all.

[0295] B: Immediately after the test ended, at least one of the whitening and foaming was slightly observed, but after being left in an environment at an ambient temperature of 25℃ for 1 hour, it was completely lost.

[0296] C: Immediately after the test ended, at least one of the whitening and foaming was slightly observed, and after being left in an environment at an ambient temperature of 25℃ for 1 hour, it did not disappear, but after 24 hours, it completely disappeared.

[0297] D: Immediately after the test ended, at least one of whitening and foaming was significantly observed, and it did not disappear even after 24 hours of standing in an environment with an ambient temperature of 25℃.

[0298] 3. Bending resistance in low-temperature environments

[0299] PET with an adhesive layer attached was cut into pieces 25mm × 150mm in size.

[0300] Next, the release film of the PET (composition: release film / adhesive layer / PET film) with the cut adhesive layer attached was peeled off, and the surface of the adhesive layer exposed by peeling was overlapped and attached to the surface of a polyimide (PI) film [product name: Kapton (registered trademark) 100H, Toray-DuPont Corp.] and then compressed using a 2kg roller to make a sample for a bending test (hereinafter referred to as "Sample Y").

[0301] A test was conducted in which the operation of bending sample Y to a radius of curvature (R) of 5 mm and then fully unfolding it was repeated 100 times under an environment with an ambient temperature of -20°C. Immediately after the test was completed, the bent sample Y was placed in a fully unfolded state under an environment with an ambient temperature of 25°C. Then, the bent portion of sample Y was observed using a magnifying glass immediately after being placed under an environment with an ambient temperature of 25°C (i.e., immediately after the test was completed), 1 hour after being placed, and 24 hours after being placed, and the bending resistance under low-temperature conditions was evaluated according to the following evaluation criteria.

[0302] It was determined that there were no practical problems if the evaluation result was "A," "B," or "C."

[0303] -metewand-

[0304] A: No change was confirmed at all.

[0305] B: Immediately after the test ended, some whitening was observed, but it completely disappeared after 1 hour of standing in an environment with an ambient temperature of 25℃.

[0306] C: Slight whitening was observed immediately after the test ended, and after being left in an environment at an ambient temperature of 25℃ for 1 hour, it did not disappear, but after 24 hours, it completely disappeared.

[0307] D: Fracture or significant whitening was observed immediately after the test ended, and it did not disappear even after 24 hours of standing in an environment at an ambient temperature of 25℃.

[0308]

[0309]

[0310] In Tables 2 and 3, “thermal shock resistance in the bent state” was simply labeled as “thermal shock resistance”.

[0311] The details of the components listed in Tables 2 and 3 are as follows.

[0312] [Crosslinking agent]

[0313] "Smidul N-75" [Trade name, Biuret-modified hexamethylene diisocyanate compound, isocyanate-based crosslinking agent, Sumika Covestro Urethane Co., Ltd.]

[0314] "Colonate L" [Trade name, Adduct of tolylene diisocyanate and trimethylolpropane, Isocyanate-based crosslinking agent, Tosoh Corporation]

[0315] The above "Smidul" and "Colonate" are both registered trademarks.

[0316] [Other ingredients]

[0317] <Tackifier>

[0318] "YS Polystar TH130" [Product Name, Terpene Phenol Resin, Yasuhara Chemical Co., Ltd.]

[0319] The above "Adecastav" is a registered trademark.

[0320] In Tables 2 and 3, “-” means that the ingredient corresponding to that column is not included.

[0321] In Tables 2 and 3, the values ​​listed in the column for “mixing amount” are all converted solid content values.

[0322] As shown in Table 2, it was confirmed that the adhesive layer formed by the adhesive compositions of Examples 1 to 15 exhibited good adhesive strength. In addition, the adhesive layer formed by the adhesive compositions of Examples 1 to 15 had excellent thermal shock resistance in a folded state. Furthermore, the adhesive layer formed by the adhesive compositions of Examples 1 to 15 had excellent bending resistance under low-temperature conditions.

[0323] Meanwhile, as shown in Table 3, the adhesive layer formed by the adhesive compositions of Comparative Examples 1 to 5 was inferior in any one of the following: adhesive strength, thermal shock resistance in a folded state, or bendability in a low-temperature environment.

Claims

Claim 1 An adhesive composition for a foldable display comprising a (meth)acrylic copolymer comprising a constituent unit derived from a monomer having a hydroxyl group and a constituent unit derived from an alkyl (meth)acrylic acid monomer (except that it comprises a constituent unit derived from a (meth)acrylic monomer having an amide group), and an isocyanate-based crosslinking agent which is hexamethylene diisocyanate, wherein when an adhesive layer is formed, the storage modulus at -20°C is in the range of 0.13 MPa or more and 0.5 MPa or less, and the ratio of the storage modulus at -20°C to the storage modulus at 100°C is in the range of 5.0 or more and 15.0 or less, and the gel fraction is 50 mass% or more (except that it is a polyrotaxane compound). Claim 2 An adhesive composition for a foldable display according to claim 1, wherein when an adhesive layer is formed, the ratio of the storage modulus at -20°C to the storage modulus at 100°C is in the range of 5.0 or more and 11.5 or less. Claim 3 An adhesive composition for a foldable display according to claim 1 or claim 2, wherein the weight average molecular weight of the (meth)acrylic copolymer is 1 million or more. Claim 4 An adhesive composition for a foldable display according to claim 1 or claim 2, wherein the glass transition temperature of the (meth)acrylic copolymer is less than -50°C. Claim 5 An adhesive composition for a foldable display according to claim 1 or claim 2, wherein the (meth)acrylic acid alkyl ester monomer comprises at least one monomer selected from the group consisting of 2-ethylhexyl acrylate and i-octyl acrylate. Claim 6 An adhesive composition for a foldable display according to claim 1 or claim 2, further comprising an adhesion promoter. Claim 7 An adhesive composition for a foldable display according to claim 1 or claim 2, wherein the (meth)acrylic copolymer comprises a constituent unit derived from a monomer having a carboxyl group in a ratio ranging from 0.5 mass% to 5 mass% with respect to the total constituent unit of the (meth)acrylic copolymer. Claim 8 An optical member for a foldable display having an adhesive layer formed by the adhesive composition for a foldable display described in claim 1 or claim 2. Claim 9 delete Claim 10 delete

Citation Information

Patent Citations

  • Adhesive for repetitive bending deice, adhesive sheet, repetitive bending laminate member and repetitive bending device

    JP2019089975A

  • Adhesive for optical film, adhesive layer for optical film, optical element, and image display device

    KR1020170062368A